Alternaria toxins in wheat during the 2004 to 2005 Argentinean harvest - Azcarate, Mariela P. (2008)
The natural occurrence of Alternaria mycotoxins in Argentinean wheat from the zone 5 South during the 2004 to 2005 harvest was investigated in 64 wheat samples. All samples were highly contaminated with a wide range of fungal species. Alternaria was found as the main component of the mycota, with an infection percentage of 100%. Three mycotoxins produced by species of Alternaria were determined in wheat: alternariol, alternariol monomethyl ether, and tenuazonic acid. Alternariol was detected in 4 (6%) of 64 samples, with a range of 645 to 1,388 μg/kg (mean of 1,054 μg/kg); alternariol monomethyl ether, with a range of 566 to 7,451 μg/kg (mean of 2,118 μg/kg) in 15 (23%) of 64 samples; and tenuazonic acid in 12 (19%) of 64 samples, with a range of 1,001 to 8,814 μg/kg (mean, 2,313 μg/kg). Alternariol monomethyl ether was the predominant toxin, but tenuazonic acid was detected in higher concentrations. Alternariol was present in fewer samples and in lower levels than were the other toxins. Tenuazonic acid a...